KAJIAN PERUBAHAN KADAR KOLESTEROL TOTAL DAN TRIGLISERIDA DARAH TIKUS WISTAR DIABETES MELALUI PEMBERIAN EKSTRAK MENGKUDU FREEZE JUICING - , PUTRI PREHATINI PAMUNGKAS, dr. Ahmad Hamim Sadewa, Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
Backround : Diabetes mellitus is one of the major health problems in the world nowadays. Diabetes mellitus effects lipid metabolism disorder called dyslipidemia where blood total cholesterol and triglyceride levels increase. Noni fruit is one of the medicinal plant which the usefulness has been known and trusted. Freeze juicing noni fruit has an opportunity to enhance the hypolipidemic effect because the active compounds in the noni fruit is less damage. Objective : Assessing the effect of freeze juicing noni fruit on total cholesterol and triglyceride levels in diabetic wistar rats. Methods :This study was an experimental study with pre and post test control group design. Thirty male wistar rats aged 2 months and weighed 160-180 grams were used. Rats fed by AIN 93 and devided into 5 groups: crontrol groups, FJ 0.25 which given freeze juicing noni fruit 0.25 ml/day, FJ 0.5 which given freeze juicing noni fruit 0.5 ml/day, and FJ 1 which given freeze juicing noni fruit 1 ml/day. The treatment carried out for 4 weeks. The blood serum was taken before and after the treatment to measure total cholesterol and triglyseride levels. And data were analyzed using One Way ANOVA test. Results : The difference total cholesterol and triglyseride levels were found, but it was not significant (p>0.05). Conclusion : Freeze juicing noni fruit has no potential effects to decrease total cholesterol and triglyceide levels in diabetic wistar rats.